Comparative Analysis of Management System Information Systems in E-learning: A Study of Indonesia and Untied States - Nadya Aisya Setiawanti; A. Mudrika; Hadi Supratikta (Journal of Investment Development, Economics and Accounting, 2024)
This study compares the implementation and effectiveness of Management Information Systems (MIS) in e-learning between Indonesia and the United States, aiming to identify unique challenges and opportunities in each country.A qualitative approach, including a systematic review of academic literature and industry publications, was used to conduct a comparative analysis of e-learning MIS in both countries.The United States benefits from advanced technological infrastructure and high digital literacy, facilitating effective MIS implementation in e-learning. Indonesia, while facing challenges like limited internet connectivity and varying digital literacy, is making progress through initiatives like Rumah Belajar and Google Classroom.This study highlights best practices from the U.S. and adaptive strategies from Indonesia, offering valuable insights for improving e-learning systems globally. It emphasizes the importance of collaboration and knowledge sharing to overcome infrastructural barriers and enhance digital literacy in developing nations.